The Role of Strategic Management in Enhancing University Performance in Indonesia: a SLR Approach - Indra Muis (Green Publisher, 2025)
Strategic management has emerged as a critical determinant of institutional success in higher education, especially in the context of dynamic policy environments and increasing global competition. This study aims to systematically review the role of strategic management in enhancing university performance in Indonesia using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A comprehensive literature search was conducted using Scopus and other reputable databases, focusing on peer-reviewed articles published between 2015 and 2025. A total of 45 studies met the inclusion criteria and were analysed for key themes, strategies, and outcomes. The findings reveal that strategic management practices-particularly strategic planning, leadership, governance, quality assurance, and innovation-significantly influence academic performance, institutional sustainability, and stakeholder satisfaction. Moreover, universities that align their strategic initiatives with national accreditation standards and digital transformation agendas tend to outperform their peers. This review highlights the urgent need for Indonesian higher education institutions to institutionalize strategic thinking as a continuous, evidence-based process. The study contributes to the growing body of literature on higher education management and offers practical insights for policymakers, university leaders, and education strategists.